MANAJEMEN BERBASIS SEKOLAH - Mahdayeni (P3M IAI Nusantara Batang Hari, 2015)
In simple terms it is understood that the school-based management is one of the government's efforts to achieve excellence Indonesian people in the mastery of science and technology . MBS is also a new paradigm of development -oriented education at school needs and the needs of each area . Great hope of course , the previous school management conditions that seem somewhat